Prognostic value of mean platelet volume/platelet count ratio in patients with resectable esophageal squamous cell carcinoma: a retrospective study - Feng, Ji-Feng (PeerJ, 2019)
BACKGROUND: Mean platelet volume (MPV) to platelet count (PC) ratio (MPV/PC) is a useful indicator in several cancers. However, the role for MPV/PC ratio in esophageal squamous cell carcinoma (ESCC) is still controversial. METHODS: A retrospective study was conducted including 277 resectable ESCC patients. The optimal cut-off values were calculated by the X-tile program. The receiver operator characteristic (ROC) curves were also created to show the candidate cut-off points. The comparisons between the X-tile plot and ROC curve were performed. The Kaplan-Meier method was utilized to analyze the cancer-specific survival (CSS). Prognostic factors for CSS were calculated with Cox regression univariate and multivariate analyses. RESULTS: According to the X-tile program, the cut-off values for MPV, PC and MPV/PC ratio were 8.5 (fl), 200 (giga/l) and 0.04, respectively. However, the cut-off values for MPV, PC and MPV/PC ratio by the ROC curves were 8.25 (fl), 243.5 (giga/l) and 0.0410, respectively. The cut-off values were similar between the X-tile and ROC curve. A low MPV/PC ratio level (≤0.04) was associated with poor CSS (22.4% vs. 43.1%, P < 0.001). In multivariate analyses, we found that MPV/PC ratio was an independent predictor for CSS (P < 0.001). When we set the cut-off point using ROC curve, the MPV/PC ratio was still an independent predictor for CSS (P < 0.001). CONCLUSION: The MPV/PC ratio is a useful predictive indicator in patients with ESCC.